Use of boron mining waste as an alternative to boric acid (H3BO3) in opaque frit production - Cicek, Bugra; Karadagli, Emirhan; Duman, Fatma (ELSEVIER SCI LTD, 2018)
Colemanite (CaO center dot 3B(2)O3 center dot 5H(2)) enrichment waste material from mines was employed as an alternative to boric acid (H3BO3) for producing opaque matt frits. The aim of the study was to reduce boric acid consumption and to substitute boron-containing waste material for H3BO3 used for frit production. Laboratory and pilot-scale production was carried out based on frit production methods currently used in the ceramic industry. The fits were then used to produce commercial glossy opaque glazes using existing fabrication and sintering processes with amounts ranging between 16 and 31 wt%. The fabricated glazes successfully passed EN ISO 10545 testing, exhibiting desirable surface abrasion, chemical resistance, thermal shock resistance, and staining characteristics.
Keywords: Borates; Waste disposal; Low temperature; Glaze; GLASS-CERAMICS; ASH; Materials Science